2021
DOI: 10.1016/j.msard.2021.103088
|View full text |Cite
|
Sign up to set email alerts
|

Higher Framingham Risk Scores are associated with greater loss of brain volume over time in multiple sclerosis

Abstract: Background: Few studies have evaluated the association between comorbidities associated with increased vascular risk and brain volume changes in multiple sclerosis (MS). To date, findings have not been consistent with respect to which comorbidities are associated with lower brain volumes or whether comorbidities associated with increased vascular risk are associated with greater brain volume loss over time. Objectives: We aimed to evaluate the association between the Framingham Risk Score (FRS) which evaluates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…As described previously ( 18 ), all participants underwent a 3 Tesla brain MRI (Siemens TIM Trio, software version VB17a, Siemens Healthcare, Erlangen, Germany; Siemens 32-channel receive-only head coil), within 4 weeks of their study visit. The images acquired included a high-resolution T1-weighted (T1w) whole brain 3D magnetization prepared rapid gradient echo (MPRAGE), dual-echo proton density-weighted (PDw), T2-weighted (T2w), fluid attenuated inversion recovery (FLAIR) images, and two 55-direction high angular resolution diffusion imaging (HARDI) scans that had phase encoding in opposite directions (see Supplementary Table e1 for scan parameters).…”
Section: Methodsmentioning
confidence: 99%
“…As described previously ( 18 ), all participants underwent a 3 Tesla brain MRI (Siemens TIM Trio, software version VB17a, Siemens Healthcare, Erlangen, Germany; Siemens 32-channel receive-only head coil), within 4 weeks of their study visit. The images acquired included a high-resolution T1-weighted (T1w) whole brain 3D magnetization prepared rapid gradient echo (MPRAGE), dual-echo proton density-weighted (PDw), T2-weighted (T2w), fluid attenuated inversion recovery (FLAIR) images, and two 55-direction high angular resolution diffusion imaging (HARDI) scans that had phase encoding in opposite directions (see Supplementary Table e1 for scan parameters).…”
Section: Methodsmentioning
confidence: 99%
“…Age was excluded from the FRS to ensure we did not confound the effect of age on cognition with the effects of vascular risk factors 19 .…”
Section: Vascular Comorbiditymentioning
confidence: 99%
“…Higher FRS scores have been associated with decreased brain volume in population-speci c samples such as older adults 18,19 and more recent ndings that reveal lower FRS scores in type 2 diabetes may be associated with better cognitive performance, as compared to those with higher FRS scores 20 . Given the increased co-occurrence of cardiovascular disease in IBD 12 , and inconsistencies in ndings of prior studies of cognition in IBD, we aimed to evaluate the association between FRS and cognitive performance in a sample of persons with IBD.…”
Section: Introductionmentioning
confidence: 95%
“…The neuroimaging protocol for the CCOMS study, which includes several advanced structural, functional, and perfusion MRI measures, was not part of the original IMID study and has not been previously reported in full (Pirzada et al, 2020;Marrie et al, 2021aMarrie et al, , 2022. Thus, the goal of the current paper is to provide a detailed overview of the neuroimaging acquisition parameters and pre-processing methods that have been employed to serve as a technical reference for subsequent study papers.…”
Section: Introductionmentioning
confidence: 99%
“…are provided in the text describing each sequence if/when appropriate. Some of the parameters for the T1w, T2-FLAIR, and PD/T2w sequences have been previously reported(Marrie et al, 2021a). Ax, Axial; EPI, Echo-Planar Imaging; FOV, Field Of View; GE, Gradient Echo; MB, Multiband; MEGE, Multi-Echo Gradient Echo; mGRASE, multi-echo gradient and spin echo; Sag, Sagittal; SE, Spin Echo; TSE, Turbo Spin Echo.…”
mentioning
confidence: 99%